High‐Surface‐Area Nitrogen‐Doped Reduced Graphene Oxide for Electric Double‐Layer Capacitors. Issue 11 (27th April 2015) - Youn, Hee‐Chang; Bak, Seong‐Min; Kim, Myeong‐Seong; Jaye, Cherno; Fischer, Daniel A.; Lee, Chang‐Wook; Yang, Xiao‐Qing; Roh, Kwang Chul; Kim, Kwang‐Bum
Abstract: A two‐step method consisting of solid‐state microwave irradiation and heat treatment under NH3 gas was used to prepare nitrogen‐doped reduced graphene oxide (N‐RGO) with a high specific surface area (1007 m 2  g −1 ), high electrical conductivity (1532 S m −1 ), and low oxygen content (1.5 wt %) for electrical double‐layer capacitor applications. The specific capacitance of N‐RGO was 291 F g −1 at a current density of 1 A g −1, and a capacitance of 261 F g −1 was retained at 50 A g −1, which indicated a very good rate capability. N‐RGO also showed excellent cycling stability and preserved 96 % of the initial specific capacitance after 100 000 cycles. Near‐edge X‐ray absorption fine‐structure spectroscopy results provided evidenced for the recovery of π conjugation in the carbon networks with the removal of oxygenated groups and revealed chemical bonding of the nitrogen atoms in N‐RGO. The good electrochemical performance of N‐RGO is attributed to its high surface area, high electrical conductivity, and low oxygen content. Abstract : Between the sheets : Nitrogen‐doped reduced graphene oxide (N‐RGO) shows excellent electrochemical performance and stability as an electrode material for electrical double‐layer capacitors due to its high surface area and electrical conductivity. The two‐step synthesis incorporates nitrogen into the hexagonal carbon lattice and restores π conjugation.